Detecção e caracterização de Escherichia coli potencialmente patogênicas em aves selvagens e pombos-domésticos na cidade de Jaboticabal-SP - Borges, Clarissa Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Escherichia coli strains that cause disease outside the intestine are known as extraintestinal pathogenic E. coli (ExPEC) and include uropathogenic E. coli (UPEC), isolated from urinary tract infections, neonatal-meningitis E. coli (NMEC), isolated from human neonates and avian pathogenic E. coli (APEC), responsible for colibacillosis in birds. These pathotypes shows similarities that suggest that the avian strains potentially have zoonotic properties. The aim of this study was to detect and characterize E. coli strains possessing virulence genes related to APEC in wild birds and pigeons, both captivity and free-living, apparently healthy. Of 500 samples collected, there were 49 isolates obtained that were analyzed by PCR for the presence of virulence genes, submitted to pathogenicity test in one day old chicks, to antimicrobial susceptibility test, serotyping, phylogenetic typing and PFGE. Virulence genes, somatic and flagellar antigens found in the isolates were previously associated to high pathogenic APEC and were also detected in human extraintestinal infections strains. Most of the isolates belonged to phylogenetic groups B1 and B2, previously described as groups that harbor pathogenic isolates from animals and the ones that cause extraintestinal infections, respectively. Furthermore, these groups had isolates with the highest number of virulence genes and highly pathogenic, while most strains of group D were no pathogenic. The captivity pigeons showed more multidrug-resistant isolates (100.0%), followed by domestic wild birds (75.0%), free-living wild birds (53.3%) and free-living pigeons (26.3%). The isolates showed high heterogeneity by PFGE, indicating that there were not E. coli prevalent clones among these birds. The results showed that wild birds and pigeons are reservoirs of multidrug-resistant E. coli harboring virulence genes related to APEC, being potentially pathogenic for humans and other animals, being able to ...

Escherichia coli que causam doenças fora do intestino são conhecidas como E. coli patogênicas extraintestinais (ExPEC) e incluem E. coli uropatogênica (UPEC), isoladas de infecção do trato urinário, E. coli associada à Meningite Neonatal (MNEC), isoladas de humanos recém-nascidos e E. coli patogênica para aves (APEC), responsável pela colibacilose aviária. Esses patótipos possuem similaridades genéticas entre si, sugerindo que APEC tenha um potencial zoonótico. O presente trabalho teve como objetivo detectar e caracterizar estirpes de E. coli que possuem genes de virulência relacionados a APEC em aves selvagens e pombos-domésticos, tanto de cativeiro quanto de vida livre, aparentemente saudáveis. Das 500 amostras, foram obtidos 49 isolados que foram analisados por PCR quanto à presença de genes de virulência, submetidos ao teste de patogenicidade in vivo, ao teste de suscetibilidade a antimicrobianos, tiveram a relação epidemiológica estabelecida por PFGE e os sorotipos e grupos filogenéticos identificados. Os genes de virulência e alguns antígenos somáticos e flagelares encontrados nos isolados foram anteriormente associados a estirpes de APEC de alta virulência e também foram detectados em ExPEC humanas. A maior parte dos isolados pertencia aos grupos filogenéticos B1 e B2, previamente descritos como grupos que albergam isolados patogênicos oriundos de animais e os que causam infecções extraintestinais, respectivamente, além disso, esses grupos possuíam os isolados com maior número de genes de virulência e de alta virulência, enquanto a maioria dos isolados do grupo D foram não virulentos. Os pombos-domésticos de cativeiro tiveram o maior número de isolados multirresistentes aos antimicrobianos (100,0%), seguido pelas aves selvagens domiciliadas (75,0%), aves selvagens de vida livre (53,3%) e pombos-domésticos de vida livre (26,3%). A análise de similaridade por PFGE mostrou alta heterogeneidade ...
Keywords: Ave; Pombo; Epidemiologia; Saúde pública; Escherichia coli; Zoonoses; Birds